2013
DOI: 10.2478/s11686-013-0158-2
|View full text |Cite
|
Sign up to set email alerts
|

First record of Aedes albopictus in Slovakia

Abstract: During a routine inspection of the mosquito fauna in the Košická Basin (Eastern Slovakia), in one of the monitored locations we have caught 4 females of the invasive mosquito Aedes albopictus, using the CO 2 baited CDC traps. Occurrence of this particular mosquito has already been reported in many European countries; in Slovakia, however, this is the first finding ever. The finding of Ae. albopictus extends the list of the mosquito fauna in Slovakia to 50 species and Slovakia thus ranks among other 20 European… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 6 publications
0
18
0
4
Order By: Relevance
“…The Dutch populations imported on lucky bamboo have not established outside greenhouses, suggesting that they are tropical strains not adapted to temperate climates, whereas populations imported from the USA via the used tyres have been supressed, so far successfully, to avoid their establishment. Specimens have also been collected at parking lots along highways and at some other places in Austria (Seidel et al, 2012), Czech Republic (Šebesta et al, 2012) and Slovakia (Bocková et al, 2013), but they seem to have so far not established as subsequent surveys remained negative. Finally, populations have recently been found in Bulgaria in 2011 (Mikov et al, 2013), Russia in 2011 (Ganushkina et al, 2012(Ganushkina et al, , 2013, Turkey in 2011 (Oter et al, 2013) and Romania (Bucarest) in 2012 (Prioteasa et al, 2013), and populations have successfully established in these countries.…”
Section: Brief History Of Spread and Potential For Future Expansionmentioning
confidence: 99%
“…The Dutch populations imported on lucky bamboo have not established outside greenhouses, suggesting that they are tropical strains not adapted to temperate climates, whereas populations imported from the USA via the used tyres have been supressed, so far successfully, to avoid their establishment. Specimens have also been collected at parking lots along highways and at some other places in Austria (Seidel et al, 2012), Czech Republic (Šebesta et al, 2012) and Slovakia (Bocková et al, 2013), but they seem to have so far not established as subsequent surveys remained negative. Finally, populations have recently been found in Bulgaria in 2011 (Mikov et al, 2013), Russia in 2011 (Ganushkina et al, 2012(Ganushkina et al, , 2013, Turkey in 2011 (Oter et al, 2013) and Romania (Bucarest) in 2012 (Prioteasa et al, 2013), and populations have successfully established in these countries.…”
Section: Brief History Of Spread and Potential For Future Expansionmentioning
confidence: 99%
“…Despite the long-term research, little attention has thus far been paid to Dirofilaria vectors. The first screening for dirofilariosis in mosquitoes was performed in 2013 and showed that the species Aedes vexans was incorporated into both the D. repens and the D. immitis life-cycles in Slovakia [ 11 , 12 ]. However, the mentioned screening was restricted only to several locations in the Košice region, in the south-eastern part of the country.…”
Section: Introductionmentioning
confidence: 99%
“…15 In Europe, Aedes albopictus has spread, after its introduction into Albania in 1979, 16 along the Mediterranean cost lines and into southern Switzerland, 17,18 southern Germany, 19 and most recently Slovakia. 20 It has also been detected in the Netherlands 21 and Belgium. 22 The presence of tiger mosquitoes in Europe, together with pathogens introduced by international travelers, represents a latent danger for transmission.…”
Section: Introductionmentioning
confidence: 86%